Coping with waste: A government-NGO collaborative governance approach in Shanghai. (1st April 2020) - Arantes, Virginie; Zou, Can; Che, Yue
Abstract: Complex environmental issues are leading local governments to collaborate with non-governmental organizations (NGOs) in the urban environmental governance sphere. While previous studies have emphasized how the Chinese government engages NGOs in service contracting to meet rising service demands, they have not provided empirical evidence of the outcomes of these collaborations at a local level. Based on a mixed methods research design developed from May 2016 to February 2017 in Shanghai, the impact of Aifen, an environmental NGO, is assessed in the context of municipal solid waste management. A total of 400 questionnaires were completed. 200 questionnaires in 10 communities where Aifen developed its activities and 200 questionnaires in 10 communities where no environmental NGO activities were accomplished. The results show that a local government-NGO collaborative governance approach enhances public participation and respond to state decentralization and rising environmental issues in urban areas. Highlights: A collaborative governance approach can enhance public participation in waste classification in urban areas. NGOs work at a local level can directly promote waste sorting behavior among urban citizens. NGOs act as effective intermediaries between State and society in the promotion of environmental governance practices. The government-NGO collaborative waste incentive program raised citizens recycling behaviors by 40%.